In-situ study of adjacent grains slip transfer of Inconel 718 during tensile process at high temperature. (April 2023) - Chen, Jutian; Lu, Junxia; Cai, Wang; Zhang, Yuefei; Wang, Yongfeng; Jiang, Wenxiang; Rizwan, Muhammad; Zhang, Ze
Highlights: The process of dislocation slip across grain boundaries activating slip systems within adjacent grains of inconel 718 alloy during the tensile at 650 °C was observed using in-situ SEM technique. A CPFEM model reflecting the microscopic morphology and lattice orientation of the alloy was developed and its reliability was verified. The evolution process of the slip systems of each grain were simulated using the model. The slip transfer at general grain boundaries and annealed twin boundaries was investigated using a combination of slip traces analysis method and CPFEM. The influence of slip systems interactions on the slip transfer was analyzed in detail. 113 results of adjacent grains slip transfer/blocking were counted, and a preliminary criterion for predicting slip transfer of inconel 718 alloy during plastic deformation at 650 °C was established. Abstract: Adjacent grains slip transfer is an important mechanism for metal adaptation to incompatibilities in intergranular deformation. Thus, this paper investigates slip transmission at grain boundaries (GBs) and annealed twin boundaries (TBs) in Inconel 718 (IN718) alloy using in-situ tensile test at 650 °C by integrating slip trace analysis and the crystal plasticity finite element method (CPFEM). Results show that the m α β criterion, based on the match of intersection lines between slip planes to GB planes and slip directions, is more reasonable in predicting induced activated slip systems than Luster-Morris m α β ′ criterion. In addition, slip transfer tended to occur at m α β ′ > 0.83 and Δ b ( 1 / b ) < 0.44 or m α β > 0.82 and Δ b ( 1 / b ) < 0.46 for general GBs; when m α β ′ > 0.92 or m α β > 0.93, continuous slip transfer is a crucial mechanism to coordinate strain and reduce stress concentration. Furthermore, the acceptable criteria for slip transfer at TBs are θ ≈ 0 and Δ b ( 1 / b ) < 0.6 by experimental and computational results. This study deepens the understanding of the adjacent grains slip transfer behavior of IN718 and also provides a new strategy to study the deformation behavior of Nickel-based superalloys. Graphical abstract: Image, graphical abstract